IoT based monitoring system for upper limb rehabilitation device - Muhammad Ikhwan, Muhammad Zulhazmi (2022)
The purpose of this project is to develop a rehabilitation device for the upper limb (finger and arm) that can be mounted on a wheelchair to ease the rehabilitation process for the patient and therapy. The purpose of this study is also to design and analysis the pain detection system for the rehabilitation device using various sensors. The target of the user of this prototype is a user with upper limb injuries or disabilities. The device requires a control system, which is pushing buttons as the manual control, and a smartphone application that has been developed to monitor the patient health condition. The development of the control system is to control the movement of dc motors that are placed under the wrist and behind the elbow and receive feedback from sensors. The sensors used are the FSR sensor also known as the force sensor. These sensors are used to give feedback control to the Arduino when the patient is feeling pain during the treatment and want to stop the movement of the device. Besides that, this project also has a heart rate sensor and DS18B20 temperature sensor. It can monitor the beat per minute (BPM) of the user and monitor the change of temperature for the user. It became essential to add temperature monitoring during the time of the pandemic of COVID-19. To follow the fast growth of the world, this study also takes part in developing a multipurpose monitoring system using the Internet of Things (IoT). App programs were researched and the most economical and easier to handle was chosen. The device uses BLYNK app inventor software with the aid of a WIFI on ESP32. At the end, this project has achieved the objectives given that the system is controlled by therapist and the patient part will move according to the therapist. The IoT system has a function to monitor heart rate, temperature and force strength that attach to human body. The IoT of the project can be further enhanced by giving a further advanced reading to the user which also can monitor their health using the apps and improving the GUI of the apps to be friendly and intelligent.